Quasispecies pattern in coronavirus along with new concern of recurrence, relapse and re-infection of SARS-CoV-2 - Kalpana, Pamayyagari (International Journal of Basic & Clinical Pharmacology, 2020)
Ever since the outbreak of pandemic novel corona virus (severe acute respiratory syndrome corona virus 2 (SARS-CoV-2)), from December 2019, researchers worldwide are working round the clock to identify the drug targets and suitable treatment options. A better knowledge of virus diversiﬁcation and evolution may be critical in preventing and treating the spread of such pathogenic viruses. This article reviews the evidences available regarding the genome sequence studies of severe acute respiratory syndrome corona virus (SARS-CoV), middle East respiratory syndrome corona virus and SARS-CoV-2 that support the quasispecies nature of virus. Further few concepts of reoccurrence, relapse and reinfection of corona virus were also summarized.